Peran Guru dalam Membimbing Anak Autisme untuk Meningkatkan Kemampuan Berkomunikasi - Selistia Oktaviani; Meilan Arsanti (UNIVERSITAS SERAMBI MEKKAH, 2024)
Autism is a spectrum of neurodevelopmental disorders that often affects an individual's communication abilities. In the context of inclusive education, the role of teachers is crucial in providing appropriate and effective support to children with autism. Teachers need to have a deep understanding of the characteristics of autism, as well as skills in identifying the unique needs and potential of each child. In addition, a learning approach that focuses on interpersonal communication and the use of adapted teaching techniques can have a positive impact in improving these children's communication skills. The research results highlight the need for an in-depth understanding of the characteristics of autism, identification of individual needs, and the implementation of tailored learning approaches to strengthen these children's interpersonal communication. It is hoped that the research findings will contribute to further understanding of the role of teachers in the context of inclusive education for children with autism.